The Effect of Giving Religious Coping Handbook Therapy on Stress and Anxiety in Final Year Students of the Bachelor of Nursing Study Program at Muhammadiyah University of Purwokerto - Uci Yuning Prapti; Siti Nurjanah (UM Purwokerto Press, 2021)
Obstacles in writing a thesis can make students experience stress, anxiety, low self-esteem, frustration, loss of motivation, and delaying writing a thesis and some even decide not to finish their thesis. Coping mechanism is a way of dealing with stress and anxiety by deceiving oneself. Religious coping is one way to deal with stress with a religious approach. The aim of this research is to determine the effect of giving religious coping handbook therapy on stress and anxiety in final year students of the Bachelor of Nursing Study Program at Muhammadiyah University of Purwokerto. This study is a pre-experimental study with a one group pretest-posttest design. Purposive sampling technique with a total of 23 respondents according to the inclusion and exclusion criteria. The research instrument used the DASS and IROPE questionnaire. Data analysis using Wilcoxon test. The results showed that the stress of students before being given therapy had an average score of 35.57 and after therapy had an average score of 6.61. Anxiety of students before being given therapy has an average score of 31.91 and after being given therapy has an average score of 4.17. There is an effect of giving religious coping handbook therapy to stress and anxiety in final year students of the Bachelor of Nursing Study Program at Muhammadiyah University of Purwokerto (p value: 0.0001). There was a decrease in stress and anxiety scores after being given religious coping handbook therapy.